Opioid Agonist Treatment and Risk of Mortality During an Opioid Overdose Public Health Emergency: A Population-Based Retrospective Cohort Study - Pearce, Lindsay A; Min, Jeong Eun; Piske, Micah; Zhou, Haoxuan; Homayra, Fahmida; Slaunwhite, Amanda; Irvine, Michael A; McGowan, Gina; Nosyk, Bohdan (International Journal of Population Data Science, 2020)
Introduction Opioid agonist treatment (OAT) is a safe and effective treatment for opioid use disorder (OUD). However, people commonly stop and start OAT and their risk of death is high immediately after stopping. The prevalence of illicitly manufactured fentanyl and other highly potent synthetic opioids have increased in the illicit drug supply globally. Yet, there is limited evidence examining the relationship between OAT and mortality when these contaminants are widely available in the illicit drug supply. Objectives and Approach We aimed to compare the risk of mortality on and off OAT in a setting with a high prevalence of illicitly manufactured fentanyl and other potent synthetic opioids in the illicit drug supply. We linked five health administrative datasets in British Columbia, Canada, creating a cohort of 55,347 people with OUD who received OAT during a 23-year period (1996 to 2018). We compared the risk of mortality on and off treatment over time, and according to time since starting or stopping treatment and by medication type. Results 7,030 of 55,347 (12.7%) OAT recipients died during follow-up. All-cause SMR was substantially lower on OAT (4.6 [4.4 to 4.8]) compared to off OAT (9.7 [9.5 to 10.0]). In a period of increasing prevalence of fentanyl, the relative risk of mortality off OAT was 2.1 [1.8 to 2.4] times higher than on OAT prior to the introduction of fentanyl, and increased to 3.4 [2.8 to 4.3] at the end of the study period (65% increase in relative risk). Conclusion / Implications The protective effect of OAT on mortality increased as fentanyl and other synthetic opioids became common in the illicit drug supply, while the risk of mortality remained high off OAT. As fentanyl becomes more widespread globally, these findings highlight the importance of interventions that improve retention on opioid agonist treatment and prevent recipients from stopping treatment.